A Cost-Utility Analysis of Nonsurgical Treatments for Stress Urinary Incontinence in Women. Issue 1 (January 2019) - Simpson, Andrea N.; Garbens, Alaina; Dossa, Fahima; Coyte, Peter C.; Baxter, Nancy N.; McDermott, Colleen D.
Abstract : Objective: The objective of this study was to perform a cost-utility analysis of nonsurgical treatments for stress urinary incontinence (SUI) in healthy adult women with a health system perspective over a 1-year time horizon. Methods: A decision tree model was constructed to evaluate the following nonsurgical treatment options for SUI in a simulated healthy adult female cohort who had failed Kegel exercises: pelvic floor muscle therapy (PFMT), a disposable tampon device (Impressa), a self-fitting intravaginal incontinence device (Uresta), and a traditional incontinence pessary. Published data and consultation with health care providers were used to estimate efficacies and costs. Health utility estimates were derived from existing literature. Deterministic sensitivity analyses were performed as well as Monte Carlo probabilistic sensitivity analysis to account for the impact of parameter uncertainty on costs and efficacies for each treatment. Our primary outcome was the highest net monetary benefit (NMB), which represents the monetary value of the health benefits less the treatment costs. The standard willingness-to-pay threshold of US $50, 000 per quality-adjusted life year was used. Results: The utility of SUI in an otherwise healthy patient was 0.81 ± 0.16 and for subjective cure was 0.93 ± 0.08. Using base-case estimates, PFMT was the most cost-effective treatment with an NMB of US $44, 098. The Impressa tampon, Uresta, and traditional pessary had NMBs of US $43, 970, $43, 785, and $42, 846, respectively. The probabilistic sensitivity analysis confirmed PFMT to be the most cost-effective treatment option at a willingness to pay of US $50, 000 per quality-adjusted life year. Conclusions: The findings of our cost-utility analysis favor PFMT as the most cost-effective nonsurgical treatment option for SUI. Cost-effectiveness for 1 year of treatment was also favorable for Impressa and Uresta. In jurisdictions where there is no public funding for PFMT, Impressa or Uresta are alternatives for women wishing to avoid surgery. Abstract : Our cost-utility analysis favors pelvic floor muscle therapy as the most cost-effective nonsurgical treatment option for stress urinary incontinence.